Evaluasi Status Kesuburan Tanah di Wilayah Desa Nanga Kebebu Kabupaten Melawi - Hazriani, Rini (Pedontropika: Jurnal Ilmu Tanah dan Sumber Daya Lahan, 2023)
Evaluation of soil fertility status in Nanga Kebubu Village Melawi District aims to describe the soil fertility on agriculture land. Collecting data of research has done by the survey that consists of land physiology survey (based on interpretation of satellite imagery and the other secondary maps) and the survey where the observation site depends on field condition of the survey area. Furthermore, the identification of nutrient status parameters is according to temporary land map unit (SPT) that has been restricted based on slope class and soil type in Nanga Kebubu Village Melawi District. Every sampel of soil unit is composed 1 kg to analyzed that consist of parameters pH, organic C, total-N, available-P, K-dd, Al-dd, cation exchangeable capacity (CEC) and basa saturated. The results of survey showed that there were 2 soil mapping units (SPT) namely SPT 2 (Typic Dystrudept) and SPT 4 (Typic Sulfaquent). Results of analysis on each SPT showed 4,08 "“ 4,41 for pH, 2,36 "“ 3,49% for organic-C, 0,27 "“ 0,39% for total-N, 33,30 "“ 41,63 ppm for available P, 0,17 "“ 0,23 mg/100g for K-dd, 33,07 "“ 34,30% for Al saturated, 13,12 "“ 17,48 cmol (+)kg-1 for CEC and 13,09 "“ 7,77% for basa saturated. Based on soil fertility criteria for paddy and rubber tree, soil fertility status is low so that it needs to be improve by location-specific fertilizer.